Correct authorship of the genus Pyrgilauda (Aves: Passeridae) - Mlíkovský, Jiří (Zootaxa, 2014)
The correct generic name and its authorship of southern snowfinches has been a matter of debate since the 1980s (Kašin 1982; Nejfel’dt 1986; Stepanân 1990) until Mlíkovský (1998) showed that Pyrgilauda is the correct generic name and that it should be attributed to Bonaparte (1850: 511), not to Verreaux (1871: 40), because Bonaparte (1850: 511) first listed that name in synonymy, because it was used as a valid name for a taxon before 1961 and because Art. 11.6.1 of the International Code of Zoological Nomenclature (ICZN 1999; hereafter the Code) applies to this case (in 1998 I referred to the then-valid Third Edition of the Code, ICZN 1985, where this Article was called "11/e").